Carbon Membranes Prepared from a Polymer Blend of Polyethylene Glycol and Polyetherimide - Wan Nurul Huda, Wan Zainal; Soon, Huat Tan; Mohd Azmier, Ahmad (Wiley, 2017)
Through a dip-coating technique, carbon membranes were produced from a polymer blend consisting of the thermally stable polymer polyetherimide (PEI) andthe thermally labile polymer polyethylene glycol (PEG). The PEG/PEI carbon membranes were synthesized on an alumina support coated with an Al2O3 intermediate layer. The polymer blend ratio and carbonization temperature influenced the structure and permeation performance of the derived carbon membranes. The porosity of the PEG/PEI carbon membranes increased with higher PEG contentin the blends. However, the derived carbon membranes tended to lose gas permeability with raising the carbonization temperatures. The carbon membranes were successfully optimized in order to achieve the highest CO2/CH4 and CO2/N2 selectivities.